2000
DOI: 10.1038/35004572
|View full text |Cite
|
Sign up to set email alerts
|

Simple rules yield complex food webs

Abstract: Several of the most ambitious theories in ecology describe food webs that document the structure of strong and weak trophic links that is responsible for ecological dynamics among diverse assemblages of species. Early mechanism-based theory asserted that food webs have little omnivory and several properties that are independent of species richness. This theory was overturned by empirical studies that found food webs to be much more complex, but these studies did not provide mechanistic explanations for the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
1,588
2
29

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,251 publications
(1,703 citation statements)
references
References 28 publications
39
1,588
2
29
Order By: Relevance
“…One major problem lies in the extent to which constituent species are 'lumped' into functional groups, in ways that can bias analysis [55]. Interestingly, Stouffer et al [56] have shown that approximately exponential degree distributions similar to those observed can be derived from at least two apparently different models proposed earlier [57,58]; this finding is reminiscent of much earlier observations that significantly different mechanisms could result in identical distributions of the relative abundance of species.…”
Section: Network Structure and Infectious Disease Dynamicsmentioning
confidence: 90%
“…One major problem lies in the extent to which constituent species are 'lumped' into functional groups, in ways that can bias analysis [55]. Interestingly, Stouffer et al [56] have shown that approximately exponential degree distributions similar to those observed can be derived from at least two apparently different models proposed earlier [57,58]; this finding is reminiscent of much earlier observations that significantly different mechanisms could result in identical distributions of the relative abundance of species.…”
Section: Network Structure and Infectious Disease Dynamicsmentioning
confidence: 90%
“…Average number of links found in a food chain across a food web [94]. Food-chain length appears to be reduced by disturbance and increased by higher energy supply and increased ecosystem size [21][22][23].…”
Section: Food Webs As a Tool For Bef Studiesmentioning
confidence: 99%
“…Food-chain length appears to be reduced by disturbance and increased by higher energy supply and increased ecosystem size [21][22][23]. Maximum chain length (max FCL) The maximum number of links found in any food chain in a food web [94].…”
Section: Food Webs As a Tool For Bef Studiesmentioning
confidence: 99%
“…Such networks, which look at the degree to which predators feed upon a prey community, can be used to observe both qualitative properties—which species are interacting—or quantitative measures that consider the strength of the species interactions (Ings et al., 2009; Williams & Martinez, 2000). While qualitative descriptors are based on the presence or absence of trophic links, quantitative metrics can include bioenergetics estimations.…”
Section: Introductionmentioning
confidence: 99%